A Moderate Dose of Alcohol Does Not Influence Experience of Social Ostracism in Hazardous Drinkers - Buckingham, Joseph; Moss, Abigail; Gyure, Krisztina; Ralph, Neil; Hindocha, Chandni; Lawn, Will; Curran, H. Valerie; Freeman, Tom P. (Frontiers in Psychology, 2016)
Anecdotal and correlational evidence suggests a relationship between social ostracism and alcohol dependence. Furthermore, a recent fMRI investigation found differences in the neural correlates associated with ostracism in people with alcohol dependence compared to healthy controls. We predicted that acutely administered alcohol would reduce the negative effects of social ostracism. Alcohol (0.4g/kg) or matched placebo was administered to a sample of 32 hazardous drinkers over two sessions in a randomized, double-blind, cross-over design. In each session, participants were exposed to an ostracism event via the computerized ball passing game, “Cyberball”. In order to quantify the effects of ostracism, the fundamental needs questionnaire was completed twice on each testing session; immediately after (i) social inclusion and (ii) social exclusion. Ostracism caused robust changes to scores on the fundamental needs questionnaire, in line with previous literature. Alcohol administration did not influence the effects of simulated social ostracism, which was supported by a Bayesian analysis. Exploratory analyses revealed a negative relationship between age and ostracism induced fundamental needs threat across both sessions. In conclusion, a moderate dose of alcohol did not influence experience of simulated social ostracism in hazardous drinkers. Further research is needed to establish the effects of alcohol administration on social ostracism using different doses and populations of alcohol users.